The Response of Cocoa Seedling (Theobroma cacao L.) Growth To Vermicompost And Terralyt – Plus Application - Wayuono, Lambang Eko Mantep; Ishartati, Erny; Rasyid, Harun (Universitas Muhammadiyah Malang, 2019)
The production of Cocoa in Indonesia is still relatively low, reached an average of 532.17 kg ha-¹, while Ivory Coast has reached 1.5 tons ha-¹ in 2013. One of the efforts to support the development of the cocoa plant is a breeding use of organic fertilizers, Vermicompost is an organic fertilizer that has a lot of nutrients and safe for plants and contains many microorganisms that needed land. While of effort to improve the performance of microorganisms in the soil by terralyt-plus. The research was conducted at the experimental farm of the Faculty of Agriculture and Animal Husbandry, University of Muhammadiyah Malang with an altitude of 560 meters above sea level, which held for 3 months. Research compiled using factorial randomized design consisting of two (2) factors. The first factor is vermicompost consists of 3 levels, namely: D0 = 0g/plant; D1 = 200g/plant and D2 = 400g/ plant. The second factor is Terralyt-plus comprises 3 levels: T0 = 0 ml/polybag, T1 = 20 ml/polybag, and T2 = 40 ml/polybag continued BNJ test with a level of 5%. Vermicompost fertilizer dosage of 400g/plant with the addition of Terralyt-plus 40ml / plants is the best treatment in all parameters of the cocoa plant (Theobroma cacao L.). Results from this study are in treatment plant height, a number of leaves and total leaf area were significantly different interactions occur while the stem diameter and the amount of chlorophyll there is no real interaction.